Transformasi Pendidikan Islam di Negara-Negara ASEAN: Antara Modernisasi Kurikulum, Tantangan Radikalisme, dan Penguatan Identitas Keislaman - Septia Fahiroh; Maryamah; Choirun Niswah (WISE Pendidikan Indonesia, 2026)
Islamic education in ASEAN is undergoing a complex transformation shaped by curriculum modernization, the prevention of radicalism, and the need to preserve Islamic identity amid globalization. This study aims to examine patterns of Islamic education transformation in Indonesia, Malaysia, Thailand, the Philippines, and Brunei Darussalam by focusing on policy orientation, curriculum reform, and institutional responses to contemporary challenges. Using library research with a qualitative-comparative approach, the study analyzes Scopus- and Web of Science-indexed journal articles, government policy documents, international agency reports, and official documents published between 2019 and 2025. The findings show that all five countries integrate moderate Islamic values into their national education systems, although the mechanisms, intensity, and degree of state intervention vary according to each country’s historical and political context. The study also finds that radicalism in Islamic educational institutions is more sustainably addressed through critical literacy and community-based preventive approaches than through purely coercive regulation. These findings imply that Islamic education reform in ASEAN should balance curriculum modernization, institutional accountability, local religious authority, and dialogical identity formation. The study concludes that Islamic education transformation in ASEAN is a multilayered negotiation between tradition, state policy, religious moderation, and global change.